Altered transversus abdominis and internal oblique muscle activation during cervical motor control tasks in individuals with chronic neck pain: A surface EMG-based analysis. - Baydogan Tan, Banu Gokcen; Tan, Sefa; Karatas, Levent; Karaoglan, Belgin (Journal of Back & Musculoskeletal Rehabilitation, 2026)
Background: Chronic neck pain (CNP) is associated with disturbances in cervical motor control and altered postural strategies. However, little is known about how cervical motor demands influence the recruitment of deep abdominal stabilizers. This study examined the activation of the transversus abdominis–internal oblique (TrA–IO) during isolated and combined cervical–trunk motor tasks in individuals with CNP. Objective: To compare TrA–IO activation during the abdominal drawing-in maneuver (ADIM) and ADIM combined with the craniocervical flexion test (CCFT) between individuals with CNP and healthy controls, and to evaluate the reliability of RMS-normalized surface EMG measurements. Methods: A total of 38 participants (19 individuals with chronic neck pain and 19 age- and sex-matched healthy controls) performed ADIM and ADIM + CCFT tasks while surface EMG recorded bilateral TrA–IO activity. EMG signals were processed using RMS and normalized to maximal voluntary isometric contraction (%MVIC). A 2 × 2 mixed-model ANOVA evaluated group and task effects. Reliability was assessed using ICC, SEM, and MDC. Results: Both groups showed increased TrA–IO activation during ADIM + CCFT compared to ADIM (p < 0.01). However, the CNP group demonstrated significantly lower activation during the combined task (left: p = 0.026; right: p < 0.001). No associations were found between EMG activation and pain, disability, or symptom duration. Reliability analyses showed excellent test–retest stability (ICC = 0.91–0.99). Conclusion: Individuals with CNP exhibit impaired ability to increase deep abdominal activation during cervical motor control tasks, indicating disrupted cervico-lumbopelvic synergy. Rehabilitation programs should integrate deep cervical flexor training with core stabilization strategies to address multi-segmental motor control deficits.